PROJECT AUTOMATION APPLICATION WITH LEAN PHILOSOPHY AT THE CONSTRUCTION OF OIL REFINING UNIT - Nascimento, Daniel Luiz Mattos; Moreira, Roger Matsumoto; Lordelo, Sandro Alberto Vianna; Caiado, Rodrigo Goyannes Gusmão; de Farias Filho, José Rodrigues; Polonia, Felipe Moret; Rodrigues, Lessandro Teixeira (Brazilian Journal of Operations & Production Management, 2016)
Increased investment in the oil industry and Brazil gas, led to the improvement in construction and assembly processes of a hydrotreating unit cracked naphtha in oil refining sub-area. Thus, the resutado achieved was mainly credited to the support of automation tools projects and principles of Lean Construction. In this way the study seeks to demonstrate the role of design automation tools, Lean philosophy and trend identified after critical analysis of the empirical study in what should be recommended for future construction and assembly, it is the sustainable logistics. Especially in the historical context of high demand for construction of oil refineries to meet the pre-salt layer in Brazil in the last 10 years. The goal is to demonstrate the results achieved through the visual management of the planning and control of construction with contrutibilidade lean principles and philosophy. This methodology is qualitative predominanemente stamp from exploratory and descriptive analysis, through bibliographic, bibliometric and experimental study in order to show barriers and benefits of utlização automation vinuladas projects tools to Lean Construction of principles with future pespectivas for logistics sustainable in the oil and gas industry